EFEK ANTI-MIKROBIAL PADA EKSTRAK CINNAMOMUM VERUM (KAYU MANIS) SEBAGAI TERAPI ADJUVANT PADA MALARIA FALCIPARUM - Isma Fadlilatus Sa'diyah (Jurnal Kesehatan, 2021)
Malaria is a major public health problem in the world, especially in Indonesia. The prevalence of malaria in Indonesia reaches 6 percent, which is mostly caused by plasmodium falciparum. Various treatment options for malaria falciparum have been developed, but due to various factors, such as the adherence to taking medication from patients are not monitored so that it can increase the risk of resistance to current malaria therapy. Therefore, the researchers conducted further research on alternative malaria therapies. Cinnamomum verum or cinnamon is known to contain cinnamaldehyde compounds which have an antimicrobial effect. The purpose of this study was to determine the anti-microbial effect of Cinnamomum verum extract or cinnamon extract as adjuvant therapy in malaria falciparum. This type of study is a literature review with the method of collecting reading results from 25 articles of case reports, research articles, and literature reviews. This study concludes that the cinnamaldehyde compound in Cinnamomum verum extraction has an antimicrobial effect which can inhibit the denaturation potential of amino acids, inhibits β-hematin formation and activity of the reductase enzyme on Plasmodium falciparum enoyl-ACP reductase, where it is known that these four have an important role. in the pathogenesis of falciparum malaria.